Fine surface treatment method of halogenated zinc phthalocyanine
By adding zinc halide phthalocyanine to NaCl-AlCl3 molten salt system and adding ester substances, the problem of easy agglomeration of zinc halide phthalocyanine pigment in humid environment and affecting its performance was solved, and green zinc phthalocyanine pigment with small particle size, good stability, strong dispersion, bright color and light resistance were prepared.
Patent Information
- Application Number
- CN202411880634.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Zinc halide phthalocyanine pigments are prone to agglomeration in humid environments, affecting their dispersion and coloring effects, and their crystal structure and surface morphology affect transparency, color brightness and light resistance.
Zinc halide phthalocyanine is added to NaCl-AlCl3 molten salt system and an ester substance is added to form zinc phthalocyanine halide with excellent surface characteristics through reaction. The reactant is then poured into deionized water to precipitate, and the finished pigment with excellent performance is obtained by filtration, water washing and drying.
A green zinc phthalocyanine pigment with small particle size, concentrated distribution, good stability, strong dispersion, excellent color brightness and light resistance was prepared, which solved the quality problems of pigments in the application of textiles, printing, inks, coatings and other fields.
Smart Images

Figure BDA0005198119140000021 
Figure BDA0005198119140000051 
Figure BDA0005198119140000052
Abstract
Description
Technical Field
[0001] The invention relates to a surface treatment method of a pigment, in particular to a fine surface treatment method of green zinc halogenide phthalocyanine (pigment). Background Art
[0002] Zinc phthalocyanine halides are an important organic pigment. According to the patent JP19970285066, zinc phthalocyanine halides are widely used in the fields of textiles, printing, inks, coatings, etc. However, zinc phthalocyanine halides have some problems in practical applications. For example, they are prone to agglomeration in a humid environment, which affects the dispersion and coloring effect of the colorant. In addition, the crystal structure and surface morphology of zinc phthalocyanine halides also affect their transparency, color brightness and light resistance. In order to solve these problems, people have improved zinc phthalocyanine pigments through surface fine treatment technology.
[0003] To solve the problem of easy agglomeration of zinc phthalocyanine halide pigments, surface treatment technology can be used, such as using surfactants or polymer coating methods to form a stable surface coating layer to prevent mutual adsorption between pigment particles, thereby improving its moisture resistance and allowing the pigment to be more stably dispersed in the medium and maintain its good dyeing effect.
[0004] In view of the crystal structure and surface morphology of zinc phthalocyanine halides, chemical synthesis can be used to allow zinc phthalocyanine halides to recrystallize and control the conditions during crystal nucleation and growth to regulate the morphology and size of the pigment crystals, thereby affecting its transparency and color vividness. At the same time, surface modification techniques, such as surface modification and nanostructure design, can also be used to regulate the morphology and structure of the pigment surface to improve its uniform deposition and color stability on the material surface, thereby improving the application effect of the pigment on materials such as textiles and plastic products. For example, in the patent JP20210514647, the inventor uses the method of recrystallizing zinc phthalocyanine halides to change its crystal form so that it can meet production requirements.
[0005] For the light resistance problem of zinc phthalocyanine halogenide pigments, surface fine treatment technology can be used, such as the introduction of surface light stabilizers, to form a surface protection layer with resistance to ultraviolet light and visible light, effectively preventing light from irradiating and oxidative damage to the pigment, improving the pigment's resistance to light attenuation, and thus extending its durability in actual use.
[0006] In recent years, research in the field of molten salt physical chemistry and electrochemistry has been very active. For example, patent KR20130011317A states that compared with aqueous solutions and organic electrolytes, the advantages of molten salt electrolytes mainly include high conductivity, fast electrode reaction speed, and high decomposition potential of molten salt electrolytes themselves. From a chemical point of view, the characteristics of haloaluminates are their structure and strong acidity. Although the aluminum bond is mainly ionic, AlCl 3 It has a tendency to generate stable dimer molecules and form non-ionized melts, so the addition of NaCl can be combined with AlCl 3 Combine to form a highly ionized liquid mixture, while lowering the overall melting point of the system.
[0007] Aiming at the problems existing in zinc phthalocyanine halides and in order to better meet the requirements of pigment quality in different fields and promote the widespread application of zinc phthalocyanine halides in the fields of textiles, printing, inks, coatings, etc., a fine surface treatment method for zinc phthalocyanine halides is proposed. Summary of the invention
[0008] The present invention aims to provide a method for fine surface treatment of zinc phthalocyanine halide.
[0009] To achieve the above purpose, the present invention adopts the following technical solution:
[0010] A fine surface treatment method for zinc phthalocyanine halides, wherein zinc phthalocyanine halides are added to NaCl-AlCl 3 The molten salt system is then added with ester substances. After the reaction, the reactants are precipitated with water to form zinc phthalocyanine halide, thus obtaining a finished pigment zinc phthalocyanine halide with excellent performance.
[0011] The zinc phthalocyanine halide is shown in the general formula I,
[0012]
[0013] In the formula, X1-X16 may be the same or different and may be selected from H, Cl, Br, and X1-X16 cannot be H at the same time.
[0014] Preferably, X1-X16 contain at least 10 halogens.
[0015] More preferably, the halogenated zinc phthalocyanine is a mixture in which the average total number of chlorine and bromine atoms is more than 15, of which the number of bromine atoms is greater than or equal to 13, and the average number of chlorine atoms is less than 2 but greater than 1.
[0016] The zinc phthalocyanine halide can be prepared according to the prior art.
[0017] Further,
[0018] Using zinc phthalocyanine halide as raw material, zinc phthalocyanine halide was gradually added to NaCl-AlCl under nitrogen protection and temperature T1. 3 The mixture system is heated to T2, and when the system is completely free of solid particles, ester substances are added to the system, and the reaction is kept warm for 2-4 hours. After cooling to T3, the reaction solution is slowly added to water, and the temperature is maintained at 20-25°C. After the addition, the mixture is kept warm and stirred for 30-50 minutes, filtered and washed with water until the conductivity of the filtrate is <20μs / cm to obtain a zinc phthalocyanine halide filter cake, which is dried to obtain a finished pigment.
[0019] The T1 is selected from 0°C-50°C;
[0020] The T2 is selected from 110°C to 150°C, preferably from 120°C to 140°C;
[0021] The T3 is selected from 30°C-50°C.
[0022] The ester substance is one or more of β-propiolactone, γ-butyrolactone, δ-valerolactone, 6-caprolactone, δ-octanolactone, and butyl undecalactone, preferably γ-butyrolactone and / or δ-valerolactone.
[0023] The NaCl-AlCl 3 Molten salt system, in which NaCl and AlCl 3 The mass ratio is 1:10-10:1, more preferably 1:8-5:2.
[0024] The zinc phthalocyanine halide accounts for NaCl-AlCl 3 Molten salt system 0.1-0.8 times (mass ratio).
[0025] The ester substance accounts for 0.01-0.2 times (molar ratio) of the zinc phthalocyanine halide.
[0026] The drying is carried out at 105° C. until the pigment solids have a water content of less than 0.5%.
[0027] The water is industrial deionized water.
[0028] The advantages of the present invention are:
[0029] The fine surface treatment method of zinc phthalocyanine of the present invention is to mix the halogenated zinc phthalocyanine into NaCl-AlCl 3 An ester substance is added to the molten system, and after the reaction is complete, the reactant is poured into deionized water to precipitate extremely fine and well-regularly dispersed zinc phthalocyanine halide. During the reaction, the existing technology is optimized by controlling the reaction parameter conditions, and a green zinc phthalocyanine pigment with excellent performance, high light transmittance and high contrast is prepared. The method of the invention has a simple process, is easy to implement, and has a very good application prospect.
[0030] The specific test method is as follows:
[0031] The specific implementation modes of the present invention are further described below in conjunction with examples. It should be noted that the specific implementation modes described here are only for illustrating and explaining the present invention, and are not limited to the present invention.
[0032] The treatment method of the present invention is to add zinc phthalocyanine halide to NaCl-AlCl 3 The molten salt system is then added with different types of ester substances to make the zinc phthalocyanine halide undergo lactone reaction, and the surface of the zinc phthalocyanine halide changes. After the reaction is complete, the reaction system is poured into deionized water to precipitate the zinc phthalocyanine halide with fine surface treatment. The product is then filtered, washed with water, and dried to obtain a finished pigment with excellent performance. The method of the present invention performs fine treatment on the surface of the zinc phthalocyanine halide pigment, that is, introduces a lactone structure, and controls the parameter conditions of the reaction to prepare a green zinc phthalocyanine pigment with small particle size and concentrated distribution, good stability, strong dispersibility, excellent color brightness and light resistance, so as to better meet the requirements of different fields for pigment quality and promote the wide application of zinc phthalocyanine halide pigments in the fields of textiles, printing, inks, coatings, etc. At the same time, the process route performs fine surface treatment on the zinc phthalocyanine halide to reduce the secondary agglomeration of the zinc phthalocyanine halide. The present invention is simple, easy to implement, and has very good application prospects.
[0033] The zinc phthalocyanine halide and deionized water used in the examples were homemade in the laboratory. 3 , NaCl, nitrogen, and the ester substances involved are all chemical reagents from Sinopharm Group.
[0034] The preparation method of zinc phthalocyanine halide used in the following examples is based on patent CN112189037A, that is, 91g of sulfuryl chloride, 109g of aluminum chloride, 15g of sodium chloride, 30g of zinc phthalocyanine, and 230g of bromine are added to a 300ml flask. The temperature is raised to 130°C and maintained at 130°C for 40h. The reaction mixture is extracted into water, filtered, washed with water, and dried to obtain a zinc phthalocyanine halide crude pigment. The pH of the filtrate washed with water is different from the pH of the washing water to ±0.2.
[0035] Example 1
[0036] In a 250 ml four-necked flask equipped with a stirrer and a condenser, 117 g NaCl (99.5%, 2 mol), AlCl 344.5g (99.5%, 0.33mol) was stirred evenly and heated to 120°C. 65g of zinc phthalocyanine halogenide solid was slowly added under stirring. The temperature was kept constant at 120°C. After the addition was completed, 1g of γ-butyrolactone was quickly added to the system. The system was kept warm for 2h and stirred rapidly. After the insulation was completed, the system was stirred continuously to allow the system to cool naturally. When the system cooled to 40°C, the reaction solution was poured into deionized water. The temperature of the reaction solution was controlled to be below 20°C. After the reaction was completed, the reaction solution was kept warm for 30min. The reaction solution was filtered and washed with water until the conductivity of the filtrate was 16μs / cm. The surface-treated zinc phthalocyanine halogenide filter cake was obtained. The pigment was dried in an oven at 105°C to obtain the finished pigment.
[0037] Example 2
[0038] In a 250 ml four-necked flask equipped with a stirrer and a condenser, 58.5 g of NaCl (99.5%, 1 mol), AlCl 3 133.5g (99.5%, 1mol) was stirred evenly and heated to 135°C. 30g of zinc phthalocyanine halogenide solid was slowly added under stirring. The temperature was kept constant at 135°C. After the addition was completed, 0.5g of δ-valerolactone was quickly added to the system. The system was kept warm for 2h and stirred rapidly. After the insulation was completed, the system was stirred continuously to allow the system to cool naturally. When the system cooled to 40°C, the reaction solution was poured into deionized water. The temperature of the reaction solution was controlled to be below 20°C. After the reaction was completed, the reaction solution was kept warm for 30min. The reaction solution was filtered and washed with water until the conductivity of the filtrate was 18μs / cm. The surface-treated zinc phthalocyanine halogenide filter cake was obtained. The pigment was dried in an oven at 105°C to obtain the finished pigment.
[0039] Comparative Example 1
[0040] 100 g of zinc phthalocyanine halide, 800 g of crushed NaCl, and 180 g of diethylene glycol were mixed in a kneader and kneaded at 90° C. for 8 hours. After kneading, the obtained mixture was placed in warm water at 60° C. for precipitation, stirred for 1 hour, filtered, and the filter cake was repeatedly rinsed, and finally the filter cake filtrate pH was 7 and the conductivity was 18 μs / cm.
[0041] Comparative Example 2
[0042] In a 250 ml four-necked flask equipped with a stirrer and a condenser, 58.5 g of NaCl (99.5%, 1 mol), AlCl 3133.5g (99.5%, 1mol) was stirred evenly and heated to 170°C. 50g of zinc phthalocyanine halogenide solid was slowly added under stirring, and the temperature was kept constant at 170°C. After the addition was completed, 5g of δ-valerolactone was quickly added to the system, and the reaction was kept warm for 2h and kept stirring rapidly. After the insulation was completed, stirring was continued to allow the system to cool naturally. When the system cooled to 40°C, the reaction solution was poured into deionized water, and the temperature of the reaction solution was controlled to be below 20°C. After pouring, the reaction solution was kept warm and stirred for 30min; filtered, washed with water until the conductivity of the filtrate was 18μs / cm, and the zinc phthalocyanine halogenide filter cake after surface treatment was obtained, and dried in an oven at 105°C to obtain the finished pigment.
[0043] The performance test analysis of the pigments was performed on Example 1, Example 2, Comparative Example 1 and Comparative Example 2 respectively, and the operation was as follows:
[0044] Primary particle size test
[0045] The average particle size of the primary particles is evaluated based on the equivalent diameter of a circle having the same area as the particle image in the photographic image observed and photographed by an electron scanning microscope (JSM-IT810), unless otherwise specified. Specifically, the equivalent diameter of the circle is calculated based on 50 particles and the average value of the diameter is used as the average particle size of the primary particles.
[0046] Secondary particle size test
[0047] First, prepare the dispersion: take 40g of the pigment to be tested and 50g of anhydrous ethanol, mix them evenly, use zirconium dioxide beads with a diameter of 0.5mm, disperse them in a sand mill (PML easy Cenomic S2) at a speed of 2000rmp for 2h, and filter them with a 5μm filter to obtain the dispersion of the corresponding pigment. Then dilute the dispersion to 15% of the initial concentration and use Malvern-zetasizerlab for dynamic light scattering particle size test
[0048] BET Test
[0049] The samples of the embodiments and comparative examples are ground into uniform powders, and then the samples are placed in a vacuum and a specific treatment temperature is set to remove the gas and moisture adsorbed on the surface. The samples are placed in an adsorption instrument (Mike ASAP2460), the liquid nitrogen temperature is set to 77.35k, and the adsorption isotherm is measured by gradually increasing the pressure of nitrogen. Under low pressure, gas molecules will be adsorbed on the surface of the sample to form a monolayer. According to the adsorption isotherm data, the BET equation is used for fitting to obtain the slope and intercept of the adsorption isotherm. According to the parameters in the BET equation, the specific surface area of the sample is calculated.
[0050] Stability test
[0051] First, prepare the dispersion: take 40g of the pigment to be tested and 50g of anhydrous ethanol, mix them evenly, use zirconium dioxide beads with a diameter of 0.5mm, disperse them in a sand mill (PML easy Cenomic S2) at a speed of 2000rmp for 2h, and filter them with a 5μm filter to obtain the dispersion of the corresponding pigment. Then, let it stand for 24 hours and 7 days and observe its sedimentation with the naked eye, and observe whether the dispersion is uniformly layered.
[0052] Light resistance test
[0053] Take 0.5g of the samples of the embodiments and comparative examples and grind them into uniform powder, then add 2g of varnish, set the flat grinder to grind 50 circles each time, grind each sample 3 times, then scrape it with a scraper, cover half of the scraped sample with black paper, and place it under a 300W xenon lamp for continuous irradiation for 6 hours to observe its fading.
[0054] Table 1 Basic performance test data of different samples
[0055]
[0056] Table 2 Application performance test data of different samples
[0057]
[0058] In summary, through NaCl-AlCl 3 The molten salt system is used to carry out fine surface treatment on zinc phthalocyanine halide, so as to prepare green zinc phthalocyanine pigment with small particle size, concentrated distribution and excellent performance. Meanwhile, a new process route is proposed to carry out fine surface treatment on zinc phthalocyanine halide and reduce the secondary agglomeration of zinc phthalocyanine halide. The invention is simple, easy to implement and has very good application prospect.
Claims
1. A fine surface treatment method for zinc phthalocyanine halide, characterized in that: The zinc phthalocyanine halide is added into the NaCl-AlCl3 molten salt system, and then the ester substance is added. After the reaction, the reactant is precipitated with water to obtain the zinc phthalocyanine halide, and the finished pigment zinc phthalocyanine halide with excellent performance is obtained.
2. The fine surface treatment method of zinc phthalocyanine halide according to claim 1, characterized in that: Using zinc phthalocyanine halide as a raw material, under nitrogen protection, at temperature T1, zinc phthalocyanine halide is gradually added to a NaCl-AlCl3 mixture system, heated to T2, and when the system is completely free of solid particles, ester substances are added to the system, and the reaction is kept warm for 2-4 hours. After the temperature is lowered to T3, the reaction solution is slowly added to water, and the temperature is maintained at 15-25°C. After the addition, the mixture is kept warm and stirred for 30-50 minutes, filtered and washed with water until the conductivity of the filtrate is less than 20μs / cm, to obtain a zinc phthalocyanine halide filter cake, which is dried to obtain a finished pigment product.
3. The fine surface treatment method of zinc phthalocyanine halide according to claim 2, The T1 is selected from 0°C-50°C; The T2 is selected from 110°C to 150°C; The T3 is selected from 30°C-50°C.
4. The fine surface treatment method of zinc phthalocyanine halide according to claim 1 or 2, characterized in that: The ester substance is one or more of β-propiolactone, γ-butyrolactone, δ-valerolactone, 6-caprolactone, δ-octanolactone, and butyl undecalactone.
5. The fine surface treatment method of zinc phthalocyanine halide according to claim 1 or 2, characterized in that: The NaCl-AlCl3 molten salt system, wherein the mass ratio of NaCl to AlCl3 is 1:10-10:
1.
6. The fine surface treatment method of zinc phthalocyanine halide according to claim 1 or 2, characterized in that: The zinc phthalocyanine halide accounts for 0.1-0.8 times (mass ratio) of the NaCl-AlCl3 molten salt system.
7. The fine surface treatment method of zinc phthalocyanine halide according to claim 1 or 2, characterized in that: The ester substance accounts for 0.01-0.2 times (molar ratio) of the zinc phthalocyanine halide.
8. The fine surface treatment method of zinc phthalocyanine halide according to claim 2, characterized in that: The drying is carried out at 105° C. until the pigment solids have a water content of less than 0.5%.
Citation Information
Patent Citations
A flux for removing calcium impurity from molten aluminium or aluminium alloy and the removing method of calcium impurity from molten aluminium or aluminium alloy using the same
KR1020130011317A
Environment-friendly preparation method of phthalocyanine green
CN108084730A
Method for producing halogenated zinc phthalocyanine pigment
CN112189037A
Method for producing pigment for color filter
CN113272389A
Process for the manufacture of polychloro-polybromo-copper phthalocyanines
GB1498054A